The phylogeographic history of a range disjunction in eastern North America: the role of post-glacial expansion into newly suitable habitat - Mohn, Rebekah (2021)
PREMISE: A disjunct distribution, where a species’ geographic range is discontinuous, can occur through vicariance or long-distance dispersal. Approximately 75 North American plant species exhibit a ~650 km disjunction between the Ozark and Appalachian regions. This disjunction is attributed to biogeographic forces including: (1) Eocene–Oligocene vicariance by the formation of the Mississippi embayment; (2) Pleistocene vicariance from interglacial flooding; (3) post-Pleistocene northward colonization from separate glacial refugia; (4) Hypsithermal vicariance due to climate fluctuations; and (5) recent long-distance dispersal. We investigated which of these pathways most likely gave rise to the Appalachian-Ozark disjunction in Delphinium exaltatum. METHODS: We genotyped populations of D. exaltatum from five Ozark and seven Appalachian localities, analyzed genetic structure, tested the order and timing of divergences using DIYABC, and conducted niche reconstructions up to 21,000 years before present (YBP). RESULTS: Populations fell into five main genetic clusters, i.e., a group in the central Appalachians, and four “lowland” groups. DIYABC analyses showed the central Appalachian and lowland lineages diverging 11,300 to17,000 YBP, and the lowland groups diverging 6800 to 10,900 YBP. Niche reconstructions showed that suitable climate for the central Appalachian lineage experienced large spatial discontinuity starting 14,000 YBP, such that divergence and persistence before this period is less plausible than divergence thereafter. CONCLUSIONS: Our results did not fully support any of the original hypotheses. Rather, the oldest divergence likely occurred after 13,500 YBP through expansion into newly opened habitat in the Appalachians. The Appalachian-Ozark disjunction likely resulted from northward dispersal of the lowland lineage as climate warmed during the Holocene.